Characterizing clinically relevant natural variants of GPCRs using computational approaches - Sengupta, Durba; Sonar, Krushna; Joshi, Manali (Methods in cell biology, 2017)
G protein-coupled receptors (GPCRs) are an important class of drug targets owing to their physiological role. A large number of clinically relevant single nucleotide polymorphisms (SNPs) have been observed in GPCRs that are linked to disease susceptibility and adverse drug response. It is therefore important to characterize the variants in order to improve GPCR therapeutics. Here, we discuss computational methods coupling molecular dynamics simulations with docking and free energy calculations to characterize the functional differences in GPCR variants. The hallmark of this approach is the explicit incorporation of receptor and membrane dynamics that allows us to analyze short- and long-range effects in the variant receptors. We use the SNPs reported in β2-adrenergic receptor (β2AR) as a test case and highlight the recent successes in analyzing structural and dynamic differences in a series of population variants. The computational approach we discuss here has a twofold benefit: it helps to unravel the molecular mechanisms underlying hypo- or hyperfunctionality of variant receptors as well as prioritizing novel variants that must be experimentally tested.

Loss of a water-mediated network results in reduced agonist affinity in a beta(2)-adrenergic receptor clinical variant - Nikte, V. Siddhanta; Sonar, Krushna; Tandale, Aditi; Joshi, Manali; Sengupta, Durba (Biochimica ET Biophysica Acta-Proteins and Proteomics, 2021)
The beta(2)-adrenergic receptor (beta(2)AR) is a member of the G protein-coupled receptor (GPCR) family that is an important drug target for asthma and COPD. Clinical studies coupled with biochemical data have identified a critical receptor variant, Thr164Ile, to have a reduced response to agonist-based therapy, although the molecular mechanism underlying this seemingly ``non-deleterious'' substitution is not clear. Here, we couple molecular dynamics simulations with network analysis and free-energy calculations to identify the molecular determinants underlying the differential drug response. We are able to identify hydration sites in the transmembrane domain that are essential to maintain the integrity of the binding site but are absent in the variant. The loss of these hydration sites in the variant correlates with perturbations in the intra-protein interaction network and rearrangements in the orthosteric ligand binding site. In conjunction, we observe an altered binding and reduced free energy of a series of agonists, in line with experimental trends. Our work identifies a functional allosteric pathway connected by specific hydration sites in beta(2)AR that has not been reported before and provides insight into water-mediated networks in GPCRs in general. Overall, the work is one of the first step towards developing variant-specific potent and selective agonists.
Keywords: beta(2)-Adrenergic receptor; G protein coupled receptor; GPCR; molecular dynamics; Pharmacogenetics; SNP

Water mediated allosteric network in beta 2AR T164I variant modulates agonist binding affinity - Nikte, Siddhanta V.; Sonar, Krushna; Tandale, Aditi; Sengupta, Durba; Joshi, Manali (European Biophysics Journal with Biophysics Letters, 2021)